FUND MANAGEMENT STRATEGIES FOR SUCCESSFUL PROPERTY INVESTMENT - Dea Mitra Ayu; Donny Dermawan (CV. ADIBA AISHA AMIRA, 2024)
An effective fund management strategy is essential to achieving success in property investment. This study explores various approaches to fund management that can maximize returns while minimizing risks associated with property investment. Using a desk-based research method, the study examines various strategies, including portfolio diversification, market analysis, risk assessment, and intelligent use of financial leverage. The findings suggest that successful property investors tend to adopt a holistic approach that takes into account macroeconomic factors, local market conditions, and socio-economic trends. In addition, an emphasis on long-term financial planning and close monitoring of investment performance are also key to achieving desired outcomes. This study provides valuable insights for investors and fund managers in developing adaptive and innovative strategies to optimize investment returns in the property sector.